Administration of Lemon Water Towards Emesis Gravidarum - Meli Doloksaribu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Hyperemesis gravidarum is a condition that is most often experienced by a pregnant woman which results in a mother having to get hospital care and treatment. Hyperemesis gravidarum generally occurs in the sixth to tenth week of pregnancy and occurs in about 60-80% of mothers with first pregnancies. Hyperemesis gravidarum not only threatens the life of pregnant women, but also has side effects on the fetus such as abortion, low birth weight and stunted fetal growth. To determine the effect of giving lemon steeping water to reduce emesis gravidarum. This type of research is Quasy Experiment with One Group Pretest Posttest. The sample is all pregnant women who experience emesis as many as 15 people with a period of 6 months. Data analysis using the T-Test Dependent statistical test. Statistical tests showed the frequency of nausea and vomiting before the intervention was given, namely 10.93 and after the intervention was given, namely 3.33 with an average decrease of 7.60. The statistical test results obtained a p-value = 0.00 (p less than 0.05) so that it can be concluded that giving lemon steeped water is effective in reducing nausea and vomiting in pregnant women. The frequency of nausea and vomiting before the intervention was given was 10.93 and after the intervention was given it was 3.33 with an average decrease of 7.60. The statistical test results obtained a p value less than 0.005 so it can be concluded that giving lemon infusion is effective in reducing nausea and vomiting in pregnant women.Abstrak: Hiperemesis gravidarum merupakan kondisi yang paling sering dialami oleh seorang ibu hamil yang mengakibatkan seorang ibu harus mendapatkan penagangan dan perawatan rumah sakit. Hiperemesis gravidarum pada umumnya terjadi pada minggu keenam sampai dengan minggu ke sepuluh kehamilan dan terjadi pada sekitar 60-80% ibu dengan kehamilan pertama. Hyperemesis gravidarum tidak hanya mengancam kehidupan ibu hamil, namun juga memberikan efek samping pada janin seperti abortus, berat badan lahir rendah, dan pertumbuhan janin terhambat. Untuk mengetahui pengaruh pemberian air seduhan lemon terhadap penurunan emesis gravidarum. Jenis penelitian Quasy Eksperimen dengan One Group Pretest Posttest. Sampel adalah seluruh ibu hamil yang mengalami emesis sebanyak 15 orang dengan waktu 6 bulan. Analisis data menggunakan uji statistik T-Test Dependent. Uji statistik menunjukkan frekuensi mual muntah sebelum diberikan intervensi yaitu 10,93 dan setelah diberikan intervensi yaitu 3,33 dengan penurunan rata-rata 7,60. Hasil uji statistik didapatkan nilai p-value=0,00 (p kurang dari 0,05) sehingga dapat disimpulkan bahwa pemberian air seduhan lemon efektif dalam penurunan mual dan muntah pada ibu hamil. Frekuensi mual dan muntah responden sebelum diberikan intervensi yaitu 10,93 dan setelah diberikan intervensi yaitu 3,33 dengan penurunan rata-rata 7,60. Hasil uji statistik didapatkan nilai p kurang dari 0,005 sehingga dapat disimpulkan bahwa pemberian seduhan lemon efektif dalam penurunan mual muntah pada ibu hamil.